Remote education and academic satisfaction of students FCCSS UNFV LIMA – 2020 - Peña Huapaya, Pedro Saturnino (2023)
The objective was to determine how remote education is related to the academic satisfaction of FCCSS UNFV 2020-1 students. The research was basic, with a descriptive scope or level and a non-experimental design. There was a population of 503 students with regular enrollment and attendance from the three schools of the Faculty of Communication Sciences. After applying probabilistic sampling there were 132 students. The results indicated that the students are not very satisfied with the dimensions: Subjects (21.3 %), Teaching 11.3 % and Contents of the syllabus (26.8 %), but with the dimensions communication and platform or virtual environment, satisfaction is average (43 %). It is concluded that a platform based on open software adapted to the reality of the FCCSS-UNFV is necessary, training for students and teachers in the use of new technologies and virtual environments. Acquire new equipment and high-speed modems to keep up with the needs of the students and the prestige of the university. Keywords: Remote education, Virtual technology, university satisfaction.